Social and Economic Motivations of Women's work and their results (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Woman has struggled for a long time through Liberation Movements and Women Associations to achieve her freedom and the equality with men to get some of her rights, and among these rights there's the right to work or work outside the home, previously women's work was only at home with some handwork and agricultural works, and here it must be pointed out that seeking women to work was the result of several motives of social and economic reasons, which led to several results that reflected on woman, family and community life.